Analisis SWOT dan Technique For Order Preference by Similarity to Ideal Solution (TOPSIS) untuk Strategi Pengembangan Usaha di Gapit 24 - Wibowo, Priyo Ari; Arofah, Meylindha Putri (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
There are many gapit industries in Cirebon area and each of these companies has a different business development strategy in dealing with change. One of them is the gapit 24 industry, where in the last few months product sales have been unstable and even tended to decline which is influenced by various factors so that it requires the right strategy to be able to maintain its business. This study aims to analyze the business development strategy of gapit 24 in Cirebon through the identification of internal and external factors. The data analysis method used is descriptive qualitative and quantitative with data collection techniques through observation, interviews, questionnaires, and literature study. Matrix analysis of IFAS and EFAS yielded 16 factors with the position of the gapit 24 business in quadrant I with an aggressive strategy and utilizing the S-O strategy. From the results of the SWOT matrix analysis, 5 alternatives are used in the S-O strategy according to business position. Data processing using the TOPSIS method obtained successive strategic priorities, alternative strategy 1, namely strengthening relationships with consumers, alternative 2, namely improve the quality of products and services, alternative 3, namely continue to innovate to introduce new products, alternative 4, namely expanding the product distribution network and alternative 5, namely identify potential business partners.